(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Information and communication technology is very important in projects management. The objective of this research is to identify and analysis the factors hindering the adoption of Information and Communication Technology (ICT) in projects management. In this research, 23 effective factors were collected from interview with engineers and experts in project managers and designers in consultant bureaus and construction companies. These factors are grouped into seven categories "Financial Factors, Human Factors, Technical Factors, Legal Factors, Administrative Factors, Cultural Factors, Security Factors ". A survey questionnaire of 75 respondents was distribute among different companies and consultant bureaus. A statistical analysis was done using SPSS and Excel packages. The relative important index was used to find out the most significant factors that hindering the adoption of ICT in projects management. The results accomplished from survey revealed that major factors hindering ICT adoption in projects management (ranked from the worst factors with Relative Important Index values, respectively) namely, Lack of training on ICT content of construction process (86.4%), Satisfaction with traditional working methods and tools (84.8%), Problem of ICT integration/compatibility with the work (82.9%), Poor interoperability between different applications/organizations (81.3%), poor quality and/or quantity of telecommunication infrastructure (81%).